Academic achievements & skills abilities tools to success - Yaacob, Solehah@Nik Najah Fadilah (2015)
I like to offer my congratulations to Scientific Institute for Advanced Training and Studies (SIATS) for their success in launching and enhancing the programs including journals publications and advance training approaches. The 1st conference on management, training and human development is the strong evidence indicates that the SIATS institute is keen to create a new environment among young people in order to create a plat form for practitioners and academicians in sharing information, knowledge, experiences and achievements. I believe Malaysia was chosen to organize this conference because of its future endeavors of training activities in human resources development and political stability system in the country. In continuing development and performance in training, we could not deny the human ability in enhancing capabilities. The concept of human development focuses on expanding the choices people have to lead life that they value and improving the human conditions. The most basic capabilities for human developments are: to lead long and healthy life, to be knowledgeable, to have access to the resources and social services needed for a decent standard of living and to be able to participate in the life of the community. Without these, many opportunities in life remain inaccessible. Thus, studying, developing and practicing which are the characteristic common to innovate leaders; foster a culture of continuous improvement, embrace life-long learning, be future facing, motivates and inspire by example, influence others by cultivate loyalty and encourage diverse thought with teams whose variety of talents, backgrounds and life experiences which facilitate innovation and creative problem solving. So, with that, I believe SIATS Institution may go out and make a positive difference to the network of people working with them and become model for the youth organization who will be the leaders of tomorrow. Good Luck! Thank You